2012
DOI: 10.1039/c2lc40360a
|View full text |Cite
|
Sign up to set email alerts
|

Droplet electroporation in microfluidics for efficient cell transformation with or without cell wall removal

Abstract: An efficient cell transformation method is presented that utilizes droplet electroporation on a microfluidic chip. Two types of green microalgae, a wall-less mutant and a wild type of Chlamydomonas reinhardtii, are used as model cells. The PDMS-glass electroporation chip is simply composed of a flow-focusing microstructure for generating cell-encapsulating droplets and a serpentine channel for better mixing of the content in the droplet, and five pairs of parallel microelectrodes on the glass slide, without in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
64
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(64 citation statements)
references
References 32 publications
(46 reference statements)
0
64
0
Order By: Relevance
“…Thus, it was recently reported that transformation efficiency in thick-walled microalgae can be improved by two orders of magnitude by electroporating them in an optimized microfluidic chamber rather than in cuvettes [83].…”
Section: Reviewmentioning
confidence: 99%
“…Thus, it was recently reported that transformation efficiency in thick-walled microalgae can be improved by two orders of magnitude by electroporating them in an optimized microfluidic chamber rather than in cuvettes [83].…”
Section: Reviewmentioning
confidence: 99%
“…The state of cell walls in strain of microalgae [18] and the composition of a liquid medium used for electroporation [11] may play also an extremely important role. Moreover, even better extraction efficiency may be expected by application of combination of conventional and electrically based techniques.…”
Section: Introductionmentioning
confidence: 99%
“…Droplet microfluidics is potentially applicable for high throughput functional screening of genes, which is not possible in the bulk electroporation process. Recently, Qu et al [76] proposed droplet electroporation with the use of microfluidic device. This device was fabricated with polydimethylsiloxane (PDMS) by using soft lithography process.…”
Section: Droplet Microfluidics For Single Cell Transfectionmentioning
confidence: 99%